Role for PKC δ in Fenretinide-Mediated Apoptosis in Lymphoid Leukemia Cells. (27th April 2010) - Ruvolo, Vivian R.; Karanjeet, Kul B.; Schuster, Todd F.; Brown, Rhoderick; Deng, Yibin; Hinchcliffe, Edward; Ruvolo, Peter P.
Abstract : The synthetic Vitamin A analog fenretinide is a promising chemotherapeutic agent. In the current paper, the role of PKCδ was examined in fenretinide-induced apoptosis in lymphoid leukemia cells. Levels of proapoptotic cleaved PKCδ positively correlated with drug sensitivity. Fenretinide promoted reactive oxygen species (ROS) generation. The antioxidant Vitamin C prevented fenretinide-induced PKCδ cleavage and protected cells from fenretinide. Suppression of PKCδ expression by shRNA sensitized cells to fenretinide-induced apoptosis possibly by a mechanism involving ROS production. A previous study demonstrated that fenretinide promotes degradation of antiapoptotic MCL-1 in ALL cells via JNK. Now we have found that fenretinide-induced MCL-1 degradation may involve PKCδ as cleavage of the kinase correlated with loss of MCL-1 even in cells when JNK was not activated. These results suggest that PKCδ may play a complex role in fenretinide-induced apoptosis and may be targeted in antileukemia strategies that utilize fenretinide.